Nanometrology - challenges for health regulation - Jailton Carreteiro Damasceno; Ana R Ribeiro; Luciene B Balottin; José Mauro Granjeiro (Fundação Oswaldo Cruz (FIOCRUZ), 2013)
The relationship between metrology, nanotechnology and nanoscience and sanitary regulation is discussed from the point of view of its importance and the interrelationship between the themes for the development of products and services involving nanotech-nology. The discussion involves the main techniques for measuring dimensional, chemical and biological properties of materials, and presents some of the challenges for the future. Issues such as processes of standardization and regulation in Europe, U.S. and Brazil are also addressed, providing an overview of how these processes are related to sanitary regulation.